2011
DOI: 10.1177/0040517511416283
|View full text |Cite
|
Sign up to set email alerts
|

Compression behavior of warp-knitted spacer fabrics for cushioning applications

Abstract: Cushioning materials generally absorb kinetic mechanical energy under compression actions at a relatively constant stress over a large range of displacement. However, cushioning materials widely used today are polyurethane (PU) foams with low moisture transmission. As a new class of three-dimensional textile structures, warp-knitted spacer fabrics not only have much better moisture transmission property than PU foams, but also have the similar cushioning performance if appropriate structural parameters are ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
117
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 6 publications
3
117
0
Order By: Relevance
“…The published studies conducted on WKSF or composites enhanced by WKSF are mainly the focus on their compressive and impact properties [11][12][13]. In these researches, WKSF showed good cushioning performance, and the great structural integrity of WKSF could prevent the clustering and bunching of reinforced fibres.…”
Section: Introductionmentioning
confidence: 99%
“…The published studies conducted on WKSF or composites enhanced by WKSF are mainly the focus on their compressive and impact properties [11][12][13]. In these researches, WKSF showed good cushioning performance, and the great structural integrity of WKSF could prevent the clustering and bunching of reinforced fibres.…”
Section: Introductionmentioning
confidence: 99%
“…As a reinforcement material, warp-knitted spacer fabrics have much better moisture transmission features [3], better resilience properties [4] and higher air permeability [5]. Moreover, composites reinforced by warp-knitted spacer fabrics exhibit superior mechanical performance compared to other textilebased composites [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of researchers has concentrated on the flexible composites based on spacer fabrics. The 3D-structure composites involved in this study possess a flexible structure, which is quite different from the composites made with stiff surfaces as shown in literatures [3][4][5][6][7][8][9][10]. The novel integrated 3D-structure composites are expected to be used for cushioning applications, such as the car seat, package materials, protection materials, and so on in order to reduce fractures after suffering compression or impact loads.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that lower monofilament inclination angle, higher fabric thickness, finer spacer yarn and larger size of surface structure meshes result in lower energy absorption in compression. [3] Du and Hu analyzed the spherical compression properties of WKSF theoretically. They investigated the deformation shape of the WKSF under spherical compression and established a relationship between total compression force and strain at the maximal compression point.…”
Section: Introductionmentioning
confidence: 99%